Efficiency boost in Si-based solar cells using tellurite glass cover layer doped with Eu3+ and silver nanoparticles - Garcia, J. A.M. [UNESP] (2019)
In this work, the relative efficiency of a solar cell covered with tellurite glasses (TeO2-ZnO and TeO2-ZnO-Na2O) doped with and without europium ions and silver (Ag) nanoparticles (NPs) placed on the top of the Si solar cell is explored. Electrical characterization was performed using a solar simulator in order to obtain the current-voltage curve at standard conditions. Efficiency results showed 12.7% enhancement with respect to a bare solar cell when europium doped: TeO2-ZnO glass with Ag NPs was used to cover the Si solar cell. Plasmonic enhancement from Ag NPs was identified as the responsible mechanism. For the case of europium doped: TeO2-ZnO-Na2O glass, it was observed an enhancement of about 11%, but in the absence of Ag NPs. The correlation between these results and the transmittance and luminescence properties of europium doped tellurite glasses, under 473 nm excitation is presented too. The present procedure represents an alternative to optimize the performance of solar cells covered by different glassy hosts. Then the efficiency enhancement of Si solar cell due to tellurite glasses doped with europium ions and Ag NPs used as cover layer opens the possibility for applications with new photovoltaic devices.